The Cambridge introduction to modern British fiction, 1950-2000 - Head, Dominic (Cambridge University Press, 2002)
Dominic Head demonstrates how the novel yields a special insight into important areas of social and cultural history in the second half of the twentieth-century. His study is the most exhaustive survey of post-war British fiction available. Placing novels in their social and historical context, it includes chapters on the state and the novel, class and social change, gender and sexual identity, national identity, and multiculturalism. Accessible and wide-ranging, this is the most current introduction to the subject available